Fuel Sources and Carbon Dioxide Emissions by Electric Power Plants in the United States - Alan W. Hodges; Mohammad Rahmani (EDIS)
FE796, a 13-page illustrated report by Alan W. Hodges and Mohammad Rahmani, summarizes trends in carbon dioxide emissions of electric power plants by type of fuel and by state in the United States during the 2003–2007 period. Includes references. Published by the UF Department of Food and Resource Economics, March 2009.